'Laughing ourselves out of the closet': comedy as a queer pedagogical form. Issue 1 (2nd January 2023) - Henry, Seán; Bryan, Audrey; Neary, Aoife
ABSTRACT: This paper explores comedy as a queer pedagogical form that subverts problematic representational tropes of queerness pervading mainstream depictions of queer experience. Articulating 'form' less as a fixed arrangement of characters, images, objects, and ideas, and more as a kind of formation that positions these in dynamic relation to the wider context in which comedies are encountered, we mobilise the idea of queer pedagogical forms to capture how comedy can foster new modes of thinking about and embodying queerness for, and with, audiences. Drawing on specific examples from Schitt's Creek and Derry Girls, we document the potential of specific comedic modalities (e.g. irony, sarcasm, irreverence, and slapstick) to foster alternative representations of queerness, in which normative tropes are poked fun at, problematised, and reimagined. Through these examples, we demonstrate how comedies can enable us to 'laugh ourselves out of the closets' we live by, feel, navigate, and embody.